The Efficiency of using Magnetized Water in Concrete: A Review (Journal of Engineering, 2024)
Concrete is globally considered the most utilized material in the world after water. Because of the increased demand for this critical material in the construction sector, researchers tend to enhance its properties by adding different additives, substituting with different pozzolanic materials (such as silica fume, glass powder, or any substance with pozzolanic activity), or changing curing methods to obtain concrete with better properties that could be employed in different applications. One of these methods is using magnetic water either by adding it to the concrete mix or by using it to cure concrete to produce concrete with improved mechanical properties. In this study, a group of articles related to the usage of magnetic water in concrete production are explained to explore the effects of magnetic water on concrete. The results showed increasing interest in this method, especially when the use of magnetic water tends to reduce the amount of cement used leading to a reduction of pollutants (indirect effect); hence, this method is considered sustainable. Also, using magnetic water could help reduce the curing time (accelerates hydration of cement). Hence, lowering both cost and time.